Educating the community about the opioid epidemic and medications for opioid use disorder. Issue 5 (11th April 2022) - Williams, Jill M.; Syed, Muzdalifa A.; Adesanya, Aderike; Gardner, George; Chaguturu, Vamsee; Coppola, Kristen M.
Abstract: Background and Objectives: Despite overwhelming evidence of benefit, medications for opioid use disorder (MOUD) remain stigmatizing and more efforts are needed to educate health care professionals and the general public. Methods: We developed and evaluated an educational program for graduate students studying health sciences, teaching them to deliver 1 h presentations to the community on the opioid crisis and the usefulness of MOUD. Results: To date, 120 graduate students have participated in this training experience on substance use disorders and delivered 59 presentations to more than 1065 community members. We found a significant increase in knowledge among students following the training. In addition, although attitudes and beliefs were generally positive at baseline, we also found significant increases in positives attitudes about the treatment of addiction and working with patients with addictions. Almost all students believed the course enhanced their professional expertise and would recommend it to others. We compared our students' baseline knowledge and attitudes to a large sample of other graduate students and did not find significant differences indicating good external validity of our results. Finally, we evaluated change in community members' knowledge and attitudes ( N = 315) following student presentations and found significant increases in knowledge and positive attitude change toward MOUD. Discussion and Conclusions: Overall our program was feasible, enjoyable, and effective in meeting its goals of increasing knowledge acquisition and improving attitudes among students and the greater community. Scientific Significance: Graduate students in health sciences can be trained to successfully teach the public about the opioid crisis and the usefulness of MOUD.